Rate of Schneiderian First Rank Symptoms among Newly Diagnosed Schizophrenic Patients - Al-Yasiri, Abdul-Rasoul; Rahim, Twana A. (AL-Kindy College Medical Journal, 2008)
Background: Schneiderian first rank symptoms are considered highly valuable in the diagnosis of schneideria. They are more evident in the acute phase of the disorder and fading gradually with time. Many studies have shown that the rate of these symptoms are variable in different countries and are colored by cultural beliefs and values. Objectives: To find out the rate of Schneiderian first rank symptoms among newly diagnosed schizophrenic patients, to assess which symptom(s) might predominate in those patients, and to find out if there is/are any correlation(s) between the occurrence of these symptoms and the sex of the patients. Methods: Out of twenty-four patients with no past psychiatric history and whom were diagnosed as Schizophrenia for their first time depending on Diagnostic and Statistical Manual-4th Edition-Text Revised criteria for diagnosis were evaluated for the presence of Schneiderian First Rank Symptoms by using a semi-structured interview schedule. Results: Out of twenty -three patients (54.7%) had present with one or more Schneiderian First Rank Symptoms.’ Third person Hallucinatory Voices", "running Commentary Hallucinatory Voices’, and " Somatic Passivity" were present more frequently than other symptoms. The study revealed no sex differences in regard of the occurrences of the Schneiderian (FRS). More than 82% of those who had the symptoms showed more than one symptom. Conclusions: Many factors influence the presence or absence of Schneiderian First Rank Symptoms among schizophrenic patients including the criteria selected for the diagnosis of the disorder, the tools adopted for the detection of these symptoms, the duration of the illness, and probably patient’s cultural background. Although there are individual differences of First Rank Symptoms among different cultures, still we expect certain symptoms to be present more than others. The influence of cultural factors in altering the basic symptoms of psychiatric illnesses is of great importance